Medication-overuse headache—a review of different treatment strategies - Krymchantowski, Abouch; Jevoux, Carla; Krymchantowski, Ana Gabriela; Ramos, Luiza Barbosa; Barbosa, Jackeline S. S.; Silva-Neto, Raimundo Pereira (Frontiers in Pain Research, 2023)
Medication-overuse headache (MOH) can develop from primary headaches. MOH is usually the result of overuse of symptomatic medications. It is a noteworthy personal and societal burden. The identification and treatment of patients at risk for MOH is an essential component of MOH management. Medication overuse can be modifiable and can advance from episodic to chronic migraine. Treatment for MOH is complex, and experts in the field have varied views on the most appropriate strategy for MOH treatment. The objective of this review is to give a comprehensive synopsis of the literature for the management of MOH. Treatment strategies, such as detoxification and prevention, are the debatable issues. Medication withdrawal is the foundation for management. The available literature suggested abrupt withdrawal with preventive approaches for early management. Bridging therapy could be useful to get relief from withdrawal symptoms. Multidisciplinary choices proved beneficial in supporting withdrawal and preventing relapse. Worldwide, the termination of overused medications has been observed as a standard treatment strategy; however, patient-specific approaches should be taken.